Incidence and Outcome of Retinopathy of Prematurity (ROP): An Observational Study from a Private Hospital in Saudi Arabia - Abdulrahman A. Al Zahrani; AbdulKarim AlMakadma; Syeda U. Naqfi; Sajjad ur Rahman; Ehab M. Hantash (Dr. Sulaiman Al Habib Medical Journal)
Objectives: This study aimed to investigate the incidence and outcomes of retinopathy of prematurity (ROP) among neonates admitted to the neonatal intensive care unit (NICU) at a private tertiary healthcare institution in Saudi Arabia. This research holds particular significance as it is the first of its kind conducted within a private tertiary care hospital in the country. Methods: This retrospective cohort study analyzes the medical records of all preterm infants admitted to our NICU in Riyadh, Saudi Arabia, between January 2023 and January 2024 who were eligible for ROP screening. We gathered data on demographics, ROP incidence, severity, and treatment outcomes. Results: In this study, a total of 105 preterm infants were screened for ROP, with an incidence rate of 31.4%. Notably, 81.8% of ROP cases regressed spontaneously, while 18.2% required treatment with laser therapy or intravitreal ranibizumab injections. The mean gestational age (GA) of infants diagnosed with ROP was 28.1 ± 2.26 weeks, and the average birth weight (BW) was 1116 ± 170 g. Factors such as lower GA, lower BW, prolonged oxygen use, and longer duration of mechanical ventilation (MV) were significantly associated with an increased incidence and severity of ROP. Conclusion: The incidence of ROP in our private tertiary care center aligns with findings from public hospitals in Saudi Arabia. This study underscores the vital role of NICU care in enhancing visual outcomes for preterm infants and highlights the urgent need for early screening and timely intervention.